Laparoscopic Ureteropelvic Junction Decompression for the Management of Obstruction - Simforoosh, Nasser; Tabibi, Ali; Nooralizadeh, Akbar; Shayani Nasab, Hamid (Urology Journal, 2009)
Purpose: We reported the outcome and complications of laparoscopic aberrant vessels transposition without performing pyeloplasty in patients with ureteropelvic stenosis. Materials and Methods: A total of 10 patients with ureteropelvic stenosis accompanying with aberrant vessels underwent laparoscopic transposition of vessels between June 2001 and March 2003. 4 of the cases were male and 6 were female, and 4 out of 10 had right side and 6 had left side involvement. The mean age was 31.9 (14 - 59). Reaction of aberrant vessels was performed by cutting the vain and fixing the artery to the lipid layer around the kidney and renal pelvis. Results: The procedure was successful in all the cases without any perioperative complications. The operative time was 2.20 hours (1.45 - 2.50) including cystoscopy, DJ placement, and transposition. Mean hospital stay was 2.9 (2-5) days, and patients were followed up an average of 9.1 (3-22) months. Except one case of rehospitalization due to pain, no complication occurred. The rate of clinical and radiological improvement was 100% and IVP showed a decrease in the degree of hydronephrosis as well as the resolution of obstruction observed in renogram. Conclusion: With regard to our findings, it seems, at least in a proportion of patients with UPJ stenosis accompanied with crossing vessels, that mechanical compression is the mere cause of obstruction and primary stenosis does not coexist. As a result, treatment is achieved by transposition of the crossing vessels without entering the renal unit.